Minority rights and minority identities - Sámi in Finland and Sorbs in Germany - Reetta, Toivanen (Finnish Yearbook of Population Research, 2001)
This paper deals with intemational minority rights and their meaning as an identityresource fr ethnic minorities. It asks why small national groups, such as the Sami andthe Sorbs, have not vanished, as was prophesied by modemisation theorists. In fact,the opposite has occurred. In Europe, small national minority groups are now clearlygaining more opportunities to invent their own "national" policies. After a short introductionthat provides some general background, 1discuss some common definitions ofminority rights and the specific meaning of 'minority identity' used in this paper. Then,1 show how minority rights and minority identities are linked to each other, and whyand how intemational minority protection treaties have become a part of the everydayvocabulary of Sami, Sorb and many other national movements. The examples 1 useoriginate mostly from my field studies with the Sorbs in Eastem Germany and the Samiin Northem Finland. 1 argue that not only the image of the group projected to itsmembers is influenced by these treaties, but that the definition of the group itself is alsochanged.